A comprehensive review on cultivation and harvesting of microalgae for biodiesel production: Environmental pollution control and future directions. (April 2020) - Yin, Zhihong; Zhu, Liandong; Li, Shuangxi; Hu, Tianyi; Chu, Ruoyu; Mo, Fan; Hu, Dan; Liu, Chenchen; Li, Bin
Graphical abstract: Highlights: Chemical, physical, biological and magnetic harvesting methods are summarized. Charge neutralisation, patching, bridging and swapping mechanisms are analyzed. Application of magnetic nanomaterials can realize the microalgae harvesting. The microalgae production can be combined with environmental pollution control. Abstract: Biodiesel is one of the best promising candidates in response to the energy crisis, since it has the capability to minimize most of the environmental problems. Microalgae, as the feedstock of third-generation biodiesel, are considered as one of the most sustainable resources. However, microalgae production for biodiesel feedstock on a large scale is still limited, because of the influences of lipid contents, biomass productivities, lipid extraction technologies, the water used in microalgae cultivation and processes of biomass harvesting. This paper firstly reviews the recent advances in microalgae cultivation and growth processes. Subsequently, current microalgae harvesting technologies are summarized and flocculation mechanisms are analyzed, while the characteristics that the ideal harvesting methods should have are summarized. This review also summarizes the environmental pollution control performances and the key challenges in future. The key suggestions and conclusions in the paper can offer a promising roadmap for the cost-effective biodiesel production.